Pengembangan Mobile Application Pembimbingan Akademik untuk Jurusan Teknik Elektro Politeknik Negeri Pontianak - Arafat, Yasir; Budianingsih, Budianingsih; Faisal, Ferry (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2024)
The vocational education system at Polnep, which implements a dropout system, either due to lack of attendance or low Semester Index Performance scores, demands the campus authorities to monitor early and continuously the academic achievement development of students. This research develops a communication and interaction medium for academic guidance, including the process of student consultations with Academic Advisor Lecturers (PA), storage of consultation records, to the recapitulation of academic guidance reports at the Department level. This mobile-based application can be used by all involved parties, namely PA Lecturers, students, and the Management in the Electrical Engineering Department of Politeknik Negeri Pontianak. The goal of this research is to provide a mobile-based application for academic guidance, facilitating communication between students and PA Lecturers in carrying out additional tasks in the Tri Dharma of Higher Education to support the improvement of students' academic performance, especially in the Electrical Engineering Department. The methodology used in this research is generally software development methodology, namely Agile Scrum. The expected outputs from the Agile Scrum methodology include system requirement documents such as Product Backlog and Sprint Backlog, along with the work results or Acceptance Deliverables from each Sprint conducted, which will ultimately form the Incremental Product to the Final Product of the developed application